Uber rider – A platform for motorcycle taxi - Ahmad Dahlan, Abdul Rahman; Saukani, Firdaus; Abdul Aziz, Mohamad Amirul Amin; Azhar, Mohamad Hazimi (EduPedia Publications (P) Ltd in Association with Other Institutional Partners, 2018)
The purpose of this project is to help and provide transportation to the needed and business to those who has motorcycle to generate income. Besides that our project also will provide transportation with better duration taken to move from one place to another place with shortest time and safety ensure to the passenger through mobile application platform Uber Rider. Uber Rider is a business model which provide a platform for person who are lazy to drive to their office or event and to those who are not able to buy a transportation. To support this project we have provided the opportunity for those who have motorcycle to generate income through this platform that we have created. Literature Reviews, Business Model Canvas (BMC), Value Proposition Design (VPD) 4 Lenses of Innovation have been used as the methodologies for this paper.